2009
DOI: 10.1016/j.acvd.2009.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Early improvement of left ventricular function after implantation of a transcutaneous aortic valve: A tissue Doppler ultrasound study

Abstract: The immediate drop in the transaortic gradient resulted in an improvement in myocardial velocities and strain, a sign of improvement in the regional systolic and diastolic regional function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Bauer et al [34] demonstrated an increase in E' and A' measured by pulsed TDI in LV septal wall but no difference in LV diastolic function measured by blood flow Doppler echocardiography when they examined the patients 24 h post-procedurally. After TAVI, our patients showed significant increases in effective orifice area and marked decreases in transvalvular pressure gradients, equivalent to a reduction in LV afterload [35].…”
Section: Discussionmentioning
confidence: 99%
“…Bauer et al [34] demonstrated an increase in E' and A' measured by pulsed TDI in LV septal wall but no difference in LV diastolic function measured by blood flow Doppler echocardiography when they examined the patients 24 h post-procedurally. After TAVI, our patients showed significant increases in effective orifice area and marked decreases in transvalvular pressure gradients, equivalent to a reduction in LV afterload [35].…”
Section: Discussionmentioning
confidence: 99%
“…The observed perioperative LV impairment is only transient as both TAVI and sAVR have been previously shown to result in improvement of LV function at later time points postprocedure 1 11. However, the transient disturbances in LV performance we describe are likely to have an impact on early postoperative recovery and may inform appropriate medical management in the immediate postprocedural period 2…”
Section: Discussionmentioning
confidence: 74%
“…However, as statin therapy did not prevent the progression of AS in multiple randomized controlled studies including ASTRONOMER, SEAS and SALTIRE, [12,19,20] it is not unexpected that the degree of diastolic dysfunction continued to progress in our patient population. Following open surgical or percutaneous aortic valve replacement, it has been shown that diastolic parameters improve in both short and long term follow-up [10,21,22]. It it also plausible that our study population may have other contributing mechanisms to progressive diastolic dysfunction including underlying asymptomatic CAD that could affect the subsequent outcome.…”
Section: Discussionmentioning
confidence: 98%